2019
DOI: 10.7196/samj.2019.v110i1.14089
|View full text |Cite
|
Sign up to set email alerts
|

Fasting plasma glucose and risk factor assessment: Comparing sensitivity and specificity in identifying gestational diabetes in urban black African women

Abstract: Background. Identifying women with gestational diabetes mellitus (GDM) allows interventions to improve perinatal outcomes. A fasting plasma glucose (FPG) level ≥5.1 mmol/L is 100% specific for a diagnosis of GDM. The International Association of Diabetes and Pregnancy Study Groups acknowledges that FPG <4.5 mmol/L is associated with a low probability of GDM. Objectives. The validity of selective screening based on the presence of risk factors was compared with the universal application of FPG ≥4.5 mmol/L to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…However, there are currently no prediction models for Africa populations and most of the existing prediction models lack external validity [ 34 ]. Recent data from Johannesburg suggest that the use of a dual-threshold fasting plasma glucose, ≥4.5mmol/L to rule out, and 5.1mmol/L to rule in GDM, may result in only 2.4% missed cases of GDM [ 21 ]. Using fasting blood glucose only for the diagnosis of HFDP will be less costly than the standard OGTT, and maybe a useful solution in the meantime.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are currently no prediction models for Africa populations and most of the existing prediction models lack external validity [ 34 ]. Recent data from Johannesburg suggest that the use of a dual-threshold fasting plasma glucose, ≥4.5mmol/L to rule out, and 5.1mmol/L to rule in GDM, may result in only 2.4% missed cases of GDM [ 21 ]. Using fasting blood glucose only for the diagnosis of HFDP will be less costly than the standard OGTT, and maybe a useful solution in the meantime.…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, recent epidemiological studies reported prevalences of HDFP and GDM of 26% [ 16 ] and 9% [ 15 ], respectively, suggesting that up to a quarter of pregnancies may be complicated by HFDP. Since most provinces in the country use a selective risk factor screening approach and consequently may miss up to 50% of women with HFDP, a substantial proportion of children are likely to be exposed to untreated HFDP [ 21 ]. This study was undertaken to contribute to the understudied area of the cardiometabolic outcomes of children from HFDP in South Africa and elsewhere in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The growing body of research in the field of HFDP over the past decade has highlighted numerous shortfalls in healthcare delivery in SA, in addition to the health burden and consequences of HFDP. [5][6][7][8][9][10][11][12][13][14] The significance of HFDP lies in the well-established short-and more recently explored long-term ramifications for both mother and child, ultimately augmenting the intergenerational risk of cardiometabolic diseases. Of profound concern is that HFDP is fuelling the type 2 diabetes mellitus (T2DM) epidemic, with over half the mothers developing diabetes within the first decade following delivery, making HFDP one of the strongest predictors of T2DM.…”
Section: In Practicementioning
confidence: 99%
“…Fortunately, there is now a growing body of research in SA highlighting the burden and risk factors for HFDP, as well as maternal, neonatal and early childhood outcomes following HFDP. [5,6,8,10,11,14,[25][26][27][28][29][30][31] The burden of HFDP in SA Urbanisation and recent socioeconomic changes in SA have fuelled a rapid nutritional transition that has been accompanied by a dramatic shift in the burden of disease from communicable diseases, such as HIV, to non-communicable diseases (NCDs) such as diabetes mellitus and HFDP. [32] Prevalence studies of HFDP for SA are limited to seven studies in the past four decades, [8,13,[26][27][28][29]33] in which the prevalence ranged from 1.8% to 25.8% owing to varying screening strategies and diagnostic tests being employed.…”
Section: In Practicementioning
confidence: 99%
“…More recently, a prospective study in South-African women confirmed that universal screening using FPG ≥ 4.5 mmol/L had greater sensitivity and specificity in identifying GDM-affected women and required fewer women to undergo a resource-intensive diagnostic OGTT than risk-factor-based selective screening. 90 Likewise, a retrospective study found that risk factor screening for GDM alone or in combination with random capillary glucose was poorly predictive of GDM, but FPG 4.8–5.0 mmol/l showed good test characteristics and resulted in a low rate of OGTTs needed. 91 A study evaluating FPG as a screening tool to rule-out GDM in a low-risk population found that women with FPG ≤3.4 mmol/L were at low risk of developing GDM with a sensitivity of 91.3%, thereby avoiding a two-step screening in 10% of their population.…”
Section: Overview Of the Included Publicationsmentioning
confidence: 99%